Data Analysis in the Internal Audit Department - Mišelnický, Tomáš (2016)
The aim of this thesis is to present a draft model for better planning internal audit engagements of branch network of the bank. The first part deals with the internal audit. It presents and discusses the definition of internal auditing by the Institute of Internal Auditors (IIA). Other relevant disciplines are also included - external audit and assurance. The importance of these disciplines is demonstrated in the example of Enron. The thesis presents the International Professional Practices Framework, especially its key components - standards. The end of this section is devoted to a description of the individual parts of an internal audit project. The second part is dedicated to planning internal audit engagements. Planning is based on the risks, therefore, there is a description of banking risks. The conclusion of this section is devoted to the process of creating the Annual Audit Plan. The final part of this work presents a model created by the author which will help to improve the planning of internal audits of the branch network of banks.